The villainess's guide to (not) falling in love. 1 - Touya; Yoimachi; Shiono, Shiori (Square Enix, Ltd., 2024)
Can one would-be villainess fend off multiple handsome suitors' advances to simply live a peaceful life? Or will the game force a happy ending no matter what? From a mundane existence to an extraordinary adventure! Luciana, once an ordinary woman, now finds herself reincarnated as the stunning villainess of an otome game. Well aware of impending plot twists, she's ready to rewrite her destiny and avoid catastrophe. She hatches a brilliant plan to live a peaceful life and avoid troublesome suitors. What could possibly go wrong? Surprise! These persistent men refuse to take a hint! And if that weren't enough, she also possesses incredible, unparalleled magical abilities. What about this world has made her so special?